Implementation of Healthy Menu Packages on Hemoglobin Levels Pregnant Women with Anemia - Fitriana Ikhtiarinawati Fajrin; Eka Sarofah Ningsih; Zuli Afifatur Rizkiyah (Healthy-Mu Journal, 2023)
The main nutritional problem that often occurs during pregnancy is anemia. The diagnosis of anemia in pregnancy can be seen from the hemoglobin (Hb) level with a lower normal value. One of the factors causing low Hb levels in pregnant women is due to poor nutritional intake. Nutritional intake can be fulfilled properly by fulfilling the food consumed by pregnant women through a healthy food menu package. This study aims to determine differences in hemoglobin levels before and after implementing a healthy menu package in pregnant women with anemia. This type of research is a Quasi Experiment using the One Group Pretest Posttest design which was carried out for 10 days for intervention. The population in this study were pregnant women who had their pregnancies checked from January to February 2023. The sampling technique was non-probability sampling using purposive sampling. Data analysis using paired t-test statistical tests. The results showed that based on the statistical test, a p-value of 0.000 was obtained (p.value <0.05). The conclusion of this study is that there is a significant difference in hemoglobin levels of pregnant women with anemia before and after giving the healthy menu package.